2016
DOI: 10.1002/14651858.cd006683.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic non-steroidal anti-inflammatory drugs for the prevention of macular oedema after cataract surgery

Abstract: Using topical NSAIDs may reduce the risk of developing macular oedema after cataract surgery, although it is possible that current estimates as to the size of this reduction are exaggerated. It is unclear the extent to which this reduction has an impact on the visual function and quality of life of patients. There is little evidence to suggest any important effect on vision after surgery. The value of adding topical NSAIDs to steroids, or using them as an alternative to topical steroids, with a view to reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 75 publications
3
54
1
6
Order By: Relevance
“…A recent Cochrane review (Lim 2016) evaluated the proportion of people with a poor vision outcome due to CME at three months after cataract surgery, with poor vision defined as 6/9 or worse attributed to a diagnosis of CME. That study found low-certainty evidence that people who received topical NSAIDs in combination with steroid may have had a lower risk of poor vision due to macular edema at three months after cataract surgery compared to those taking corticosteroids alone (RR 0.40, 95% CI 0.27 to 0.61).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review (Lim 2016) evaluated the proportion of people with a poor vision outcome due to CME at three months after cataract surgery, with poor vision defined as 6/9 or worse attributed to a diagnosis of CME. That study found low-certainty evidence that people who received topical NSAIDs in combination with steroid may have had a lower risk of poor vision due to macular edema at three months after cataract surgery compared to those taking corticosteroids alone (RR 0.40, 95% CI 0.27 to 0.61).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two recent Cochrane systematic reviews studied the effectiveness of topical NSAIDs, either alone or in addition to topical corticosteroids, vs topical corticosteroids alone. Although they found low certainty evidence to suggest some risk reduction of PCMO using NSAID (with or without corticosteroids) there was no definite evidence to suggest the superiority of NSAIDs with or without adjunctive corticosteroids in relation to the prophylaxis of PCMO …”
Section: Prophylaxismentioning
confidence: 99%
“…In addition, concerns of drug tolerability differences between NSAIDs and corticosteroids have emerged (Duong et al 2014;Kessel et al 2014;Kim et al 2015;Cardascia et al 2016;Coassin et al 2016;Grzybowski et al 2016;Lim et al 2016;Malik et al 2016;Duan et al 2017;Pollack et al 2017). The main interest revolves around the question whether the choice between topical corticosteroids or nonsteroidal anti-inflammatory drug (NSAID) affects postoperative inflammation or the risk of developing pseudophakic cystoid macular oedema (PCME; also, known as Irvine-Gass syndrome), and whether the choice has an impact on the speed of visual recovery and acuity gain.…”
Section: Introductionmentioning
confidence: 99%